Evaluation of therapeutic effects of crocin in attenuating the progression of diabetic nephropathy: a preliminary randomized triple-blind placebo-controlled trial - Asma Jaafarinia; Behzad Kafami; Adeleh Sahebnasagh; Fatemeh Saghafi (BMC, 2022)
Abstract Background Diabetic nephropathy (DN) is one of the most important complications of type 2 diabetes (T2DM). Oxidative stress and inflammatory cytokines play an essential role in the development and progression of DN. Despite adopting appropriate therapies, many patients with DN progress to end-stage renal disease (ESRD). Therefore, exploring innovative strategies for better management of DN is crucial. Crocin, a natural compound found in saffron, has profound antioxidant, antifibrotic and anti-inflammatory properties. This study aimed to evaluate the therapeutic effects of crocin in attenuation of the progression of DN. Methods In this randomized, triple-blind, placebo-controlled clinical trial, 44 patients with T2DM and microalbuminuria were randomly assigned to receive either crocin (15 mg/day) or a placebo for 90 days. Eventually, 40 patients completed the study: 21 patients in the crocin group and 19 in the placebo group. The primary outcome was a change in urine Albumin-to-Creatinine Ratio (uACR) from baseline to the end of the treatment period. We also evaluated metabolic, anthropometric, and biochemical parameters as the secondary outcomes. Results The results of the present study showed that uACR increased in both groups, but the increment was not significantly higher in the crocin group compared with the placebo. Serum levels of transforming growth factor-β (TGF-β) decreased in the crocin group and increased in the placebo group, but none of these changes was significant. Crocin significantly reduced triglyceride (TG) as an important metabolic parameter (P-Value = 0.03). Conclusion This study has shown that crocin may be a safe and potential adjunct to conventional therapies for DN patients but because of our limitations such as short duration of the treatment period, and prescribing low doses of crocin, we could not achieve the significant level.